Evaluation of hyperglycaemic risk of atorvastatin: a dose dependent study on hyperlipidaemic rats - Prashanth Kumar, T. E.; S., Mahammad Juber; M., Swetha Vijetha (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Statins (β-hydroxy β-methylglutaryl-CoA (HMG-CoA) reductase inhibitors) are the most prescribed medications worldwide to treat hyperlipidaemia with a proven ability to reduce major cardiovascular events. Recent data have revealed that statin therapy is associated with an increased risk for developing diabetes. The risk was most significant in patients taking atorvastatin, rosuvastatin and simvastatin. Methods: Rats were divided into 3 groups, each comprising of 6 rats. Hyperlipidaemia was induced in all the animals after feeding with high fat diet for 15 days. Rats of groups 1, 2 and 3 were given atorvastatin 1.8 mg/kg (low-dose), 3.6 mg/kg (moderate-dose) and 7.2 mg/kg (intensive-dose) respectively orally for 60 days. 12 hours fasted blood samples were collected and analyzed for serum lipid profile, fasting blood glucose and HbA1c levels. Results: The percentage increase in plasma blood glucose after 60 days of treatment in groups 1, 2, and 3 is 29.93%, 60.03% and 72.42% respectively and the variation in all the groups is statistically significant, p<0.0001. Regarding HbA1c values, the variation in low-dose group is statistically insignificant whereas the percentage increase in moderate-dose and intensive-dose groups is 19.45% (p<0.001) and 43.37% (p<0.0001) respectively. Conclusions: In conclusion, there is significant increase in blood glucose and HbA1c levels leading to new-onset diabetes in both moderate-dose and intensive-dose groups. The risk is more in intensive-dose group when compared to moderate-dose group.